ANALYSIS OF BRAND IMAGE STRATEGIES ON INSTAGRAM IN REACHING THE MARKET: CASE STUDY ON SAMBAL CAK MAN - Himam, Nadiah Sabrina (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
This research is aimed at analyzing the effectiveness of brand image strategies on the Instagram platform in reaching a wider market for Sambal Cak Man products. The method used in this research is descriptive qualitative. In this study, researchers carried out data collection steps using in-depth interviews, observation and documentation. The results of this research show that the brand image strategy on the Instagram platform is effective in expanding the Sambal Cak Man market as proven by the number of orders from outside the region to outside the province after using Instagram as a marketing medium.